2017
DOI: 10.1016/j.jaci.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils are a major source of the epithelial barrier disrupting cytokine oncostatin M in patients with mucosal airways disease

Abstract: Background We have previously shown that Oncostatin M (OSM) is elevated in nasal polyps of chronic rhinosinusitis (CRS) patients, as well as in bronchoalveolar lavage (BAL) fluids after segmental allergen challenge in allergic asthmatics. We also showed in vitro that physiological levels of OSM impair barrier function in differentiated airway epithelium. Objective We sought to determine which hematopoietic or resident cell type(s) were the source of the OSM expressed in mucosal airways disease. Methods Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 56 publications
(75 reference statements)
2
98
0
1
Order By: Relevance
“…35,37,53 A study on patients in Chicago discovered that nasal polyps, which are highly eosinophilic, also have significant levels of neutrophils. 61 Interestingly when comparing subjects with IL-17 + and those with IL-17 − inflammation, or comparing IFN-γ + with IFN-γ − subjects in Caucasians, the IL-17 + and IFN-γ + groups consistently had significantly higher levels of MPO and IL-1β, indicating a contribution of types 1 and 3 immune responses to the development of neutrophilic inflammation. 26 The recently published study by Wang et al demonstrated that increased production and activation of epithelial cell-derived IL-36γ may act on neutrophils and further amplify neutrophilic inflammation in CRS (Fig 2).…”
Section: Immune Polarization In Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…35,37,53 A study on patients in Chicago discovered that nasal polyps, which are highly eosinophilic, also have significant levels of neutrophils. 61 Interestingly when comparing subjects with IL-17 + and those with IL-17 − inflammation, or comparing IFN-γ + with IFN-γ − subjects in Caucasians, the IL-17 + and IFN-γ + groups consistently had significantly higher levels of MPO and IL-1β, indicating a contribution of types 1 and 3 immune responses to the development of neutrophilic inflammation. 26 The recently published study by Wang et al demonstrated that increased production and activation of epithelial cell-derived IL-36γ may act on neutrophils and further amplify neutrophilic inflammation in CRS (Fig 2).…”
Section: Immune Polarization In Crsmentioning
confidence: 99%
“…64 Neutrophils have been suggested to impair epithelial barrier function as well, potentially through releasing oncostatin M, an epithelial barrier disrupting cytokine. 61 IFN-γ was reported to induce activated but insufficient autophagy, leading to p62-dependent apoptosis of nasal epithelial cells in CRSwNP. 65 In addition, impaired autophagy in myeloid cells was reported to aggravate eosinophilia, epithelial hyperplasia, and mucosal thickening in mice with eosinophilic CRS.…”
Section: Epithelial Barrier Defect and Reduced Innate Immunity In Crsmentioning
confidence: 99%
“…One study showed neutrophils to be a major source of the cytokine Oncostatin M, which affected epithelial barrier function in the airways of patients with severe asthma or in those with chronic rhinosinusitis [98]. …”
Section: Beneficial and Adverse Effects Of Neutrophils In The Asthmatmentioning
confidence: 99%
“…OSM-producing haematopoietic cells include T cells, monocytes, macrophages, dendritic cells, neutrophils, eosinophils and mast cells. 11,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Although the mechanisms that regulate OSM expression are not extensively characterized, several investigators have reported STAT5-dependent induction of OSM expression, particularly when acting downstream of leukemogenic mutations, including the FIP1L1-PDGFRA fusion protein and hyperactive mutant forms of JAK2, KIT and FLT3. [62][63][64][65] Similarly, OSM expression can be induced in a STAT5-dependent fashion by other cytokines, including erythropoietin (Epo), G-CSF (granulocyte colony-stimulating factor), IL-2 and IL-3.…”
Section: Regulation Of Osm Productionmentioning
confidence: 99%